Influence of landscape environmental settings on outdoor pedestrian thermal comfort in tropical climate - Kasim, Zanariah; Shahidan, Mohd Fairuz; Ujang, Norsidah; Dahlan, Nur Dalilah (Universiti Putra Malaysia Press, 2019)
A suitable microclimate can increase pedestrian comfort and encourage walkability and support sustainability. This study aimed at measuring the effectiveness of selected types of Landscape Environmental Settings for Pedestrian (LESP) in influencing the thermal comfort in tropical campus environments. Field measurement data was collected under 5 different types of LESP in a university campus. The types are; No shade (T1), Metal deck (T2), One row of trees (T3), Combined deck and trees (T4), and Two rows of trees (T5). Pedestrian thermal comfort is assessed by measuring i) Air temperature (Ta), ii) Globe temperature (Tg), iii) Wind velocity (v), iv) Surface temperature (Ts), and v) Relative humidity (Rh). Data were analysed and ranked according to the comfort level of the pedestrians. Results indicate the importance of natural and man-made shading and pavement materials on pedestrians’ comfort. Shading can reduce the temperature of pavements even from low albedo materials such as dark grey asphalts and contribute to pedestrian thermal comfort. The findings can be helpful for landscape architects and urban planners in specifying appropriate microclimatic interventions to improve pedestrian comfort in the tropical environment.